Simulasi Analisis Kekuatan Struktur Komposit Honeycomb Sandwich Berpenguat Jenis Serat Batang Pisang dan Serat Kaca - Rivaldi Rivaldi; Kardiman Kardiman; Aa Santosa (Jurnal Ilmiah Wahana Pendidikan, 2022)
In this study, the sandwich structure is known as a core attached to two rigid and strong shells; The core distributes the load from one shell to another. While the skin contributes to bending and turgidity, adhesives that carry shear and axial loads to the core material are used as bonding agents. As a binder in this composite used polyester resin. The honeycomb sandwich panels made are 50mm high and 50mm wide, while the panel lengths are made in three variations, namely with honeycomb lengths of 50mm, 75mm and 100mm. This honeycomb sandwich panel was tested by bending test to obtain flexural strength and stiffness values. Of the three panels that were made identically for each honeycomb core height, the highest flexural strength and stiffness figures were obtained in the panel with a honeycomb core height of 50mm, namely with a flexural strength number of 5.08kg/mm2 and a stiffness value of 12.74kg/mm.